Effects of MEH-PPV Molecular Ordering in the Emitting Layer on the Luminescence Efficiency of Organic Light-Emitting Diodes - Seok Je Lee; Jun Li; Seung Il Lee; Chang-Bum Moon; Woo Young Kim; Jin Cao; Chul Gyu Jhun (Molecules, 2021)
We investigated the effects of molecular ordering on the electro-optical characteristics of organic light-emitting diodes (OLEDs) with an emission layer (EML) of poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene] (MEH-PPV). The EML was fabricated by a solution process which can make molecules ordered. The performance of the OLED devices with the molecular ordering method was compared to that obtained through fabrication by a conventional spin coating method. The turn-on voltage and the luminance of the conventional OLEDs were 5 V and 34.75 cd/m2, whereas those of the proposed OLEDs were 4.5 V and 120.3 cd/m2, respectively. The underlying mechanism of the higher efficiency with ordered molecules was observed by analyzing the properties of the EML layer using AFM, SE, XRD, and an LCR meter. We confirmed that the electrical properties of the organic thin film can be improved by controlling the molecular ordering of the EML, which plays an important role in the electrical characteristics of the OLED.